Technological Resistance and Cultural Continuity in Indigeneous Kampung Adat Kuta - Friskawati , Gina Eka; Rianto, Puji (Asian Journal of Media and Communication, 2024)
The penetration of communication technology in rural areas and indigenous villages has been massive since modernization in the 1960s. However, not all communities are willing to adopt these technological innovations. Instead, they resist because the technology is not following the traditional values that develop in the community. This research investigates how the community of Kuta Traditional Village in Ciamis Regency resists technology, specifically modern communication technology. The research was conducted qualitatively. Data were collected through in-depth interviews with the community and community leaders. Data were also supplemented through observations in Kampung Adat Kuta. The results showed that the community faced a dilemma in resisting the presence of modern communication technology. The dilemma mainly occurs due to differences between generations in responding to the presence of modern communication technology. While the older and younger generations still believe that modern communication technology should not be used in Kuta Traditional Village, many of the younger generations have left the village to use modern communication technology. This research shows the complexity of the community in dealing with the presence of modern communication technology, and how culture and generation ultimately determine the forms of community acceptance.